Associative recognition in a patient with selective hippocampal lesions and relatively normal item recognition - Mayes, A.R.; Holdstock, J.S.; Isaac, C.L.; Montaldi, D.; Grigor, J.; Gummer, A.; Cariga, P.; Downes, J.J.; Tsivilis, D.; Gaffan, D.; Gong, Qiyong; Norman, K.A. (Hippocampus, 2004)
Previous work (Mayes et al., Hippocampus 12:325–340, 2002) found that patient YR, who suffered a selective bilateral lesion to the hippocampus in 1986, showed relatively preserved verbal and visual item recognition memory in the face of clearly impaired verbal and visual recall. In this study, we found that YR's Yes/No as well as forced‐choice recognition of both intra‐item associations and associations between items of the same kind was as well preserved as her item recognition memory. In contrast, YR was clearly impaired, and more so than she was on the above kinds of recognition, at recognition of associations between different kinds of information. Thus, her recognition memory for associations between objects and their locations, words and their temporal positions, visual items or words and their temporal order, animal pictures and names of professions, faces and voices, faces and spoken names, words and definitions, and pictures and sounds, was clearly impaired. Several of the different information associative recognition tests at which YR was impaired could be compared with related item or inter‐item association recognition tests of similar difficulty that she performed relatively normally around the same time. It is suggested that YR's familiarity memory for items, intra‐item associations, and associations between items of the same kind was mediated by her intact medial temporal lobe cortices and was preserved, whereas her hippocampally mediated recall/recollection of these kinds of information was impaired. It is also suggested that the components of associations between different kinds of information are represented in distinct neocortical regions and that initially they only converge for memory processing within the hippocampus. No familiarity memory may exist in normal subjects for such associations, and, if so, YR's often chance recognition occurred because of her severe recall/recollection deficit. Conflicting data and views are discussed, and the way in which recall as well as item and associative recognition need to be systematically explored in patients with apparently selective hippocampal lesions, in order to resolve existing conflicts, is outlined. © 2004 Wiley‐Liss, Inc.